2018
DOI: 10.4103/jips.jips_295_17
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength of hydrogen plasma-treated polypropylene fiber-reinforced polymethyl methacrylate denture base material

Abstract: Hydrogen plasma treatment on polypropylene fiber has a significant role in enhancing the adhesion between PMMA polymer matrix and the polypropylene fibers and thereby the flexural strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In contrast, a study by Yu et al [38] showed increased FS and FT at 5.3 wt.% and 7.9 wt.% loadings of GL/UHMWPE fibers. Additionally, a study by Mathew et al [52] demonstrated statistically higher FS at 10 wt.% loadings of hydrogen plasma-treated polypropylene fibers. The other studies either claimed no effect on FS [29] or reported enhanced FM, SH, or CS at elevated filler loading levels [43,44,50].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, a study by Yu et al [38] showed increased FS and FT at 5.3 wt.% and 7.9 wt.% loadings of GL/UHMWPE fibers. Additionally, a study by Mathew et al [52] demonstrated statistically higher FS at 10 wt.% loadings of hydrogen plasma-treated polypropylene fibers. The other studies either claimed no effect on FS [29] or reported enhanced FM, SH, or CS at elevated filler loading levels [43,44,50].…”
Section: Discussionmentioning
confidence: 93%
“…All of these studies used nano-sized particles, except for Al-Bakri et al [35], in which 1.5 µm sized glass fillers were used. Glass fibers and other types of polymeric fibers were of also interest to investigators [31,32,34,[37][38][39][40][41]51,52]. There was less of an inclination towards the use of minerals such as mica, borax, boric acid, and colemanite as reinforcing agents in denture base resin [43,53].…”
Section: Discussionmentioning
confidence: 99%
“…Mathew et al 14 suggested that among the PPF reinforced test group (3, 6, and 12 mm length of the fiber and 2.5, 5, and 10 wt%), a 6 mm long fiber reinforced in 2.5 wt% resulted in the best flexural strength value. In addition, Mathew et al 13 suggested that fiber weight percentage, fiber length, and adhesion between fiber and matrix play an important role in flexural characteristics of the hydrogen plasma‑treated PPF‑reinforced PMMA polymer. In the present study, 5 wt% added PPF supports the study conducted by Mathew et al that the addition of PPF 5 and 10 wt% is required to get better mechanical properties coupled with an easy and cost‑effective reinforcing procedure.…”
Section: Discussionmentioning
confidence: 99%
“…PPF is widely used in surgery because of low density, high strength, and high biocompatible. 13 In addition, they enable the natural looking and biocompatible strengthening properties of PMMA. 4 In the literature, limited studies focused on strengthening of PMMA with PPF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation